Sunflower in Romanian agriculture - Csép, Nicolae (Acta Agraria Debreceniensis, 2018)
Romania is one of the largest producers of sunflower closely followed by Bulgaria, Hungary, France and Spain. The total sunflower production increased after 1990, due the increase of cultivated surface during the moderate yield average increasing rate. Last year, Romania was ranked first in the European Union (EU) for the area cultivated with sunflower and the total production of sunflower seeds, according to the National Statistics Institute (INS). Romania’s position on the map of sunflower producers area is supported by about 1 million hectares sown. In the segment of sunflower productivity, Romania has an unfavourable position, situated in the last places in the classification of the EU’s most productive agricultures. In order to increase production per hectare, it is required to perform measures aimed at the elements of sustainable cultivation technology, including the stability of the production level by ensuring phytosanitary protection.